PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN - Ulfah, Putri Armala; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out the influence of cash flow, account receivable turnover, and inventory turnover to the profitability on food and beverages companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods. The independent variables i.e. cash turnover, account receivable turnover, and inventory turnover. Meanwhile, the dependent variable is profitability.The samples are 9 companies. The sample collection technique has been done by using purposive sampling. The research method of this research is quantitative method. The data of this research is the secondary data in the form of financial statement which has been obtained from Indonesia Stock Exchange (IDX). The analysis technique has been carried out by using multiple linear regressions analysis.The result of the research shows that cash flow turnover and account receivable turnover give influence to the profitability whereas inventory turnover does not have any influence to the profitability. The value of adjusted R square is 0.348 shows that all independent variables i.e. cash flow turnover, account receivable turnover, and inventory turnover can explain the dependent variable i.e. profitability which is 34.8% and the remaining is 65.2% is influenced by other factors which are not included in the models.Keywords: Profitability, cash flow turnover, account receivable turnover, inventory turnover.